2010
DOI: 10.1002/lary.21291
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in the treatment of idiopathic sudden sensorineural hearing loss

Abstract: Zinc supplementation may enhance the hearing recovery of SSNHL patients. Its antioxidant and anti-inflammatory effects may help reduce the oxidative stress of the cochlea in SSNHL, implying a new direction in the treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 36 publications
2
40
0
5
Order By: Relevance
“…The causes of most cases of SSNHL cannot be identified and are thought to be idiopathic. Although spontaneous recovery may occur in some patients with sudden hearing loss, many different treatment regiments have been suggested (1), including corticosteroids, antiviral drugs, vasoactive agents, and antioxidants (2). Among these, systemic steroids are commonly used as a standard therapy (3).…”
mentioning
confidence: 99%
“…The causes of most cases of SSNHL cannot be identified and are thought to be idiopathic. Although spontaneous recovery may occur in some patients with sudden hearing loss, many different treatment regiments have been suggested (1), including corticosteroids, antiviral drugs, vasoactive agents, and antioxidants (2). Among these, systemic steroids are commonly used as a standard therapy (3).…”
mentioning
confidence: 99%
“…Moreover, it is an expensive and time-consuming treatment method. Other possible options include medications such as antiviral agents [23], vasodilators (such as carbogen, alprostadil, naftidrofuryl, and low-molecular-weight dextran) [24], high-dose vitamins [25], [26], and zinc supplementation [27]. However, the effects of these agents have not been sufficiently studied and there is no evidence to support their use.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc has been studied as a supplemental therapy to standard oral steroid therapy in two trials. The earlier study found that patients in the zinc group had greater improvement in hearing gain after therapy, and serum zinc levels were correlated to post‐treatment PTA . A more recent study was unable to replicate these findings, and instead showed that zinc supplementation had no significant improvement in PTA or speech discrimination scores (SDS) compared with systemic steroids alone .…”
Section: Other (Nonsteroidal) Therapiesmentioning
confidence: 96%
“…The earlier study found that patients in the zinc group had greater improvement in hearing gain after therapy, and serum zinc levels were correlated to post-treatment PTA. 26 A more recent study was unable to replicate these findings, and instead showed that zinc supplementation had no significant improvement in PTA or speech discrimination scores (SDS) compared with systemic steroids alone. 27 No consensus exists on the use of zinc or magnesium in the management of SSNHL to date, as they are not explicitly mentioned in practice guidelines.…”
Section: Mineral Therapies (Zinc)mentioning
confidence: 96%
See 1 more Smart Citation